1995
DOI: 10.1063/1.468740
|View full text |Cite
|
Sign up to set email alerts
|

Fast energy delocalization upon vibrational relaxation of a deuterated zeolite surface hydroxyl

Abstract: . (1995). Fast energy delocalization upon vibrational relaxation of a deuterated zeolite surface hydroxyl. Chemical Physics, 102(5), 2181-2185. DOI: 10.1063/1.468740 General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

1995
1995
1997
1997

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 25 publications
3
29
0
Order By: Relevance
“…At the O-D wavelength our laser pulses have a much smaller spectral width than at the O-H wavelengths, which results in a better signal-to-noise ratio and an improved frequency resolution 42 ͑see Table I for an overview of the experimental parameters and the results͒. Furthermore, we will show later that for the O-D experiments spectral diffusion is negligible ͑due to lower concentrations of oscillators and smaller transition dipole moments compared to the O-H vibrations͒.…”
Section: A Vibrational Dynamics Of O-d: T 1 Lifetimes and Homogeneoumentioning
confidence: 99%
See 2 more Smart Citations
“…At the O-D wavelength our laser pulses have a much smaller spectral width than at the O-H wavelengths, which results in a better signal-to-noise ratio and an improved frequency resolution 42 ͑see Table I for an overview of the experimental parameters and the results͒. Furthermore, we will show later that for the O-D experiments spectral diffusion is negligible ͑due to lower concentrations of oscillators and smaller transition dipole moments compared to the O-H vibrations͒.…”
Section: A Vibrational Dynamics Of O-d: T 1 Lifetimes and Homogeneoumentioning
confidence: 99%
“…44 Catalytically active sites in the porous zeolite framework are the hydroxyl groups, which are found near aluminum atoms in the crystalline alumino-silicate structure. The time-resolved infrared saturation experiments provided new information on the different hydroxyl groups and hydrogen bonding to the lattice, 37,38 on the deexcitation mechanism, 42 and on interactions with adsorbates. 43 Besides contributing to the insight in the molecular structure, these studies are the very first step in revealing the reaction dynamics on a molecular scale, since the coordinate of the hydroxyl stretch vibration is parallel with the reaction coordinate for the catalytic proton donation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is demonstrated by the transmission increase after vibrational relaxation, which means that OD... N 2 groups have been converted to bare OD groups with a different frequency. However, experiments with decreasing pump energy revealed that the desorption is indirect, caused by a rapid heating of the zeolite lattice due to the laser pulse [8,9]. Hence, in contrast to other hydrogen-bonded systems, direct dissociation of the hydrogen bond as a one-photon desorption process, does not occur upon relaxation of the vibrationally excited zeolite hydroxyl.…”
Section: The Effect Of the Adsorbate On The Relaxation Ratementioning
confidence: 98%
“…Knowledge of the interaction between BrOnsted hydroxyls and adsorbed species is therefore essential for a fundamental understanding of zeolite catalysis. Time-resolved infrared spectroscopy has proven to be a powerful tool in the investigation of the vibrational dynamics of the zeolite hydroxyl [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. This paper reports on a time-resolved infrared investigation of the effect of simple adsorbates on the dynamic properties of the catalytic BrOnsted hydroxyl.…”
Section: Zeolite Samplesmentioning
confidence: 99%